2020
DOI: 10.1186/s12885-020-06780-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of concurrent chemoradiotherapy in ECOG 2 patients with locally advanced non-small-cell lung cancer: a subgroup analysis of a randomized phase III trial

Abstract: Background: There is no consensus on the therapeutic approach to ECOG 2 patients with locally advanced non-smallcell lung cancer (LA-NSCLC), despite the sizable percentage of these patients in clinical practice. This study focused on the efficacy, toxicity and the optimal chemotherapy regimen of CCRT in ECOG 2 patients in a phase III trial. Methods: Patients capable of all self-care with bed rest for less than 50% of daytime were classified as ECOG 2 subgroup. A subgroup analysis was performed for ECOG 2 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The median OS for the Eastern Cooperative Oncology Group (ECOG) 0–1 arm was 30.1 months, compared to 16.4 months for the ECOG 2 arm ( p < 0.001). 27 We also confirmed that PS (KPS score) prior to therapy had a significant impact on survival.…”
Section: Discussionsupporting
confidence: 76%
“…The median OS for the Eastern Cooperative Oncology Group (ECOG) 0–1 arm was 30.1 months, compared to 16.4 months for the ECOG 2 arm ( p < 0.001). 27 We also confirmed that PS (KPS score) prior to therapy had a significant impact on survival.…”
Section: Discussionsupporting
confidence: 76%
“…The median OS for the Eastern Cooperative Oncology Group (ECOG) 0-1 arm was 30.1 months, compared to 16.4 months for the ECOG 2 arm (P< 0.001). [23] We also con rmed that performance status (KPS score) prior to therapy had a signi cant impact on survival.…”
Section: Discussionsupporting
confidence: 52%
“…Several real‐world adjuvant durvalumab trials included small groups of patients with ECOG performance status ≥2 without identifying these patients at risk for worse outcomes or increased risk of AE. 12 , 15 Bi et al 23 showed no difference in treatment compliance, toxicities, or outcomes between patients with ECOG 2 and ECOG 0–1 performance scores receiving chemoradiation for stage III NSCLC. Two of four patients with ECOG performance scores ≥2 that were included in our durvalumab cohort remain alive and free of disease, suggesting adjuvant durvalumab may also benefit patients with ECOG performance scores ≥2.…”
Section: Discussionmentioning
confidence: 98%